THE EFFECTIVENESS OF THE INTERLACED WAVES STRATEGY IN MATHEMATICAL ACHIEVEMENT AMONG FIRST-GRADE INTERMEDIATE STUDENTS - Zainab Haider Bidn Al- Turfy, Ayat Mohammed Jebur Rana Sabih Abboud (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Abstract The research aims to state: (the effectiveness of the interlaced waves strategy in mathematical achievement among first- grade intermediate students). To verify the objective of the research, the following null hypotheses were formulated: There is no statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group who will study according to the strategy of overlapping waves and the scores of the students of the control group who will study according to the usual method in the mathematical achievement test. H0 = H1 = H2 There is no statistically significant difference at the level of significance (0.05) for the overlapping wave strategy, according to Kuhn’s equation for the size of the effect on the study variable.